Konstruksi Konjektur Siswa secara Kolaboratif berbantuan Geogebra - Rahmadhani, Yanti Nur; Rosyidi, Abdul Haris (MATHEdunesa, 2025)
Reasoning and proof are part of mathematical activities. One of the activities of reasoning and proof is constructing conjectures. In several studies, students' skills in constructing conjectures are still lacking. Conjecture construction can be maximized through collaborative discussions. Geogebra helps students in visualization, construction, and discovery of concepts. This study aims to describe students' conjecture construction collaboratively assisted by Geogebra on the topic of. This study is a qualitative descriptive study. Data were obtained through assignments and interviews. The subjects in this study were 4 groups divided into high homogeneity, medium homogeneity, low homogeneity, and heterogeneity groups. Conjecture construction was analyzed based on the stages of (1) understanding the problem, (2) exploring the problem, (3) formulating conjectures, (4) justifying conjectures, and (5) proving conjectures. The result showed t the stage of understanding the problem, all groups can determine what is requested and what is given even though there are still errors. At the problem exploration stage, all groups illustrate problems on Geogebra, they also explore using tools on Geogebra the group is highly homogeneous and is having discussions in exploring problems At the stage of designing the conjecture, they discussed with their group to create a conjecture from the exploration results, but the low homogeneity and heterogeneous groups prepared the conjecture without discussion. All groups can explain the reasons for the conjectures that have been made. At the stage of proving the conjecture, only highly homogeneous and moderately homogeneous groups allow the conjecture. At the stage of proving the conjecture, their proof structure was incomplete, they only described one example of the conjecture they made.